+0  
 
0
107
1
avatar+81 

Rewrite the expression

 

\(\ln (a+b) + 4 \ln (a-b) - 3 \ln c\)

 

as a single logarithm \(\ln A.\) . Then the function A=

Sloan  Jun 7, 2018

Best Answer 

 #1
avatar
+1

Ln A = Ln {[(a+b)(a-b)^4]/(c^3)}

 

A = [(a+b)(a-b)^4]/(c^3)

Guest Jun 7, 2018
 #1
avatar
+1
Best Answer

Ln A = Ln {[(a+b)(a-b)^4]/(c^3)}

 

A = [(a+b)(a-b)^4]/(c^3)

Guest Jun 7, 2018

37 Online Users

avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.